The Influence of Compensation and Collaborative Leadership of Principals on Teachers' Work Morale at SDN 20 Mandau - Wijaya, Herlina; Masrul, Masrul; Wahyuni, Molli (Journal of English Language and Education, 2025)
This study aims to determine the effect of compensation and collaborative leadership of the principal on teacher work enthusiasm. This study uses a quantitative approach with a quasi-experimental research type and multiple linear regression analysis techniques. The population of the study was all teachers at SDN 20 Mandau, with a sample of 12 teachers taken by total sampling. The research instrument was a questionnaire with a Likert scale and an observation sheet. The results of the study showed that partially compensation did have a significant effect on teacher work enthusiasm, with a significance value of 0.004 0.05 and a t-count of 3,349 t table (2.201) so that Ho was reject. On the other hand, the collaborative leadership of the principal had a significant effect on teacher work enthusiasm with a significance value of 0.000 0.05 and a t-count of 5.401 t table (2.201) so that Ho was rejected. Simultaneously, the compensation and collaborative leadership variables of the principal had a significant effect on teacher work enthusiasm. This is proven by the significance value of 0.001 0.05, and the Fcount value of 14.823 Ftable of 4.84. Thus, the better the collaborative leadership of the principal and the more adequate the compensation received by teachers, the higher the teacher's work enthusiasm.